Proceedings IEEE Southeastcon '92
DOI: 10.1109/secon.1992.202317
|View full text |Cite
|
Sign up to set email alerts
|

Neural network-based classification of electromyographic (EMG) signal during dynamic muscle contraction

Abstract: A neural network-based decision making tool was developed for on-line classification of various neuromuscular diseases. Intramuscular electromyographic (EMG) signals were collected using microcomputer-based real-time data acquisition system during voluntary human muscle contraction. The data was collected from three different group of patients. A number of signal processing techniques such as: Autoregressive (AR) modeling, Short Time Fourier Transform (STFT), Wigner-Ville Distribution (WVD), and Chaos analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Chaos is a complex motion which is always restricted in limited areas, extremely sensitive to initial values, long-term unpredictable, with track never repeated, fractal dimension and strange attractors. Amount of study demonstrated that Center Nervous System (CNS) generates chaotic firing patterns of action potentials; and a variety of physiological potential nerve signals, including EEG, ECG and EMG, etc., originated from CNS, have shown some degree of chaotic behavior, too [16][17][18][19][20][21][22][23][24][25][26][27][28]. Some nonlinear analysis methods are applied to the analysis of EMG.…”
Section: Chaotic Theory Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaos is a complex motion which is always restricted in limited areas, extremely sensitive to initial values, long-term unpredictable, with track never repeated, fractal dimension and strange attractors. Amount of study demonstrated that Center Nervous System (CNS) generates chaotic firing patterns of action potentials; and a variety of physiological potential nerve signals, including EEG, ECG and EMG, etc., originated from CNS, have shown some degree of chaotic behavior, too [16][17][18][19][20][21][22][23][24][25][26][27][28]. Some nonlinear analysis methods are applied to the analysis of EMG.…”
Section: Chaotic Theory Analysis Methodsmentioning
confidence: 99%
“…Bodruzzaman et al extracted fractal dimension [18], Hurst's rescaledrange, Housdorff-Besicovich fractal dimension [19] and correlation dimension [20] respectively, to analyze sEMG acquired from the patients with neuromuscular diseases. The results indicated that chaotic features of sEMG are effective indicators for diseases diagnosis.…”
Section: Introductionmentioning
confidence: 99%